Seismic fragility of tall concrete wall structures in Malaysia under near-field earthquakes considering inadequate splice length - Mohammad Masoud Masoomi, 1988-, author 631448; Sophia C. Alih, 1980-, supervisor 257008; Mohammadreza Vafaei, 1978-, supervisor 545356; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam 619085 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Thesis (Sarjana Kejuruteraan (Struktur))